Integrating peace education in pre-service teachers training programs: views from teacher educators and prospective teachers in Pakistan / Sufi Amin, Nabi Bux Jumani and Samina Malik - Amin, Sufi; Jumani, Nabi Bux; Malik, Samina (Universiti Teknologi MARA Cawangan Sarawak, 2019)
Peace education is one of the emerging developments of the 21st century in teacher education all over the world. The objective of the study is to investigate the views of teacher educators and prospective teachers regarding peace education in teacher education in Pakistan. The research design employed in this study is quantitative survey research. The population of the present study comprised all teacher educators as well as prospective teachers of five universities in Islamabad, Pakistan. Sample of the study consisted of 280 teacher educators and prospective teachers. Simple random sampling technique was used in the selection of the sample. The questionnaire was used as research instrument. The validity of the research instrument was ensured with the help of experts. Following recommendations from the experts, the research instrument was modified. The reliability of the instrument was assessed. The researchers distributed 280 questionnaires and 255 questionnaires were received. The data were analyzed with the help of SPSS (Version, 20). A modern Statistical method expressed in percentage, frequency and Mean Score was used for data analysis and interpretation. It was concluded that peace education develops positive thinking among teachers, develops knowledge of human rights, develops the quality of self-awareness among teachers, promotes justice and compassion among teachers, as well as endorses justice in society